AGROCHEMICAL RETAILERS AS CHANGE AGENTS: A BEHAVIOURAL STUDY ON THEIR WILLINGNESS TO PROMOTE BIO-PESTICIDES AND ORGANIC INPUTS - Faiz, Abul (International Journal of Research -GRANTHAALAYAH, 2025)
Agrochemical retailers serve as a vital link between manufacturers and farmers, often influencing decisions related to pesticide use. With the growing need for sustainable agriculture, the promotion of bio-pesticides and organic inputs is critical. However, limited attention has been paid to the behavioural determinants behind retailers’ product recommendations. This study investigates the willingness of pesticide retailers to promote eco-friendly alternatives such as bio-pesticides and organic inputs in Kamrup district, Assam, India. Using a mixed-method approach involving surveys and interviews with 50 retailers, the study reveals that while most retailers are aware of bio-pesticides, their willingness to promote them is often constrained by perceived low demand, lack of incentives, insufficient technical knowledge and concerns over product efficacy. The study concludes with policy recommendations aimed at strengthening retailers' capacity as change agents for sustainable agriculture.